A report on seven fetal cases associated with 15q11‐q13 microdeletion and microduplication. Issue 3 (4th February 2021) - Huang, Xiuzhu; Chen, Jieping; Hu, Wenlong; Li, Lu; He, Huiyan; Guo, Hui; Liao, Qiuyan; Ye, Mei; Tang, Donge; Dai, Yong
Abstract: Background: The 15q11‐q13 region contains three breakpoints (BP1 to BP3), and copy number variations often occur in the region. Aims: 15q11‐q13 microdeletion and microduplication are usually associated with Prader‐Willi and Angelman syndromes, respectively. It is not yet clear to what extent microdeletion and microduplication affect the physical health of the fetus and the child. In this study, we examined seven fetuses ranging in gestational age from 15 to 27 weeks. Materials & Methods: Detailed prenatal screening and laboratory examinations were performed, while karyotype analysis and chromosomal microarray analysis (CMA) of the amniotic fluid and umbilical cord blood were applied for genetic analysis. Results: CMA analysis showed that four fetuses harbored a microdeletion and one fetus showed a microduplication at 15q11.2 BP1‐BP2, two fetuses had a microdeletion at 15q11‐q13 BP2‐BP3, and one fetus had an additional microdeletion at 16p13.11. Discussion: There is no clear standard for the clinical diagnosis of 15q11‐q13 microdeletion and microduplication, some of them have clinical phenotypes or are clinically affected. Conclusion: Therefore, parents of such fetuses should be informed of the possibility of microdeletions or microduplications to mitigate the psychological burden, and medical consultation and assistance should be provided when communicating the results of the mid‐gestation screening. Abstract : All seven fetal cases in this report have 15q11‐q13 microdeletions and microduplications of different sizes, but not all of them have clinical phenotypes or are clinically affected.